Alpha-1 Antitrypsin Deficiency and Lung Cancer Risk. Issue 9 (September 2015) - Torres-Durán, María; Ruano-Ravina, Alberto; Parente-Lamelas, Isaura; Abal-Arca, José; Leiro-Fernández, Virginia; Montero-Martínez, Carmen; Pena, Carolina; Castro-Añón, Olalla; Golpe-Gómez, Antonio; González-Barcala, Francisco J.; Martínez, Cristina; Guzmán-Taveras, Rosirys; et al.
<x xml:space="preserve">Abstract</x> Background: Never-smokers comprise up to 25% of all lung cancer cases. They could have different molecular pathways for lung cancer induction compared with smokers. Alpha-1 antitrypsin (AAT) deficiency is a hereditary trait whose main characteristic is early onset of lung emphysema. Our aim is to know if AAT-deficient carriers have a higher risk of lung cancer in a study performed exclusively in never-smokers. Methods: We designed a multicentre hospital-based case–control study, which included incident never-smoking lung cancer cases. Controls were never-smokers attending nonmajor surgery at the participating hospitals. Controls were frequency matched on age and gender with cases. We determined AAT variants (alleles S and Z) through polymerase chain reaction. Results: Two hundred and twelve cases and 318 controls were included. PiSS individuals showed a lung cancer risk of 4.64 (95% confidence interval: 1.08–19.92) compared with those with normal genotype (PiMM). When the analysis was restricted to women, the risk for PiSS increased to 7.58 (95% confidence interval: 1.40–40.87). This risk for homozygous SS was even higher for individuals exposed to environmental tobacco smoke (greater than 20 years). The presence of other alleles did not show any effect on lung cancer risk. Conclusions: Never smoking SS homozygous individuals pose an increased risk of lung cancer. The risk is higher for individuals exposed to environmental tobacco smoke.